The physiological effects of a diet free of meat and egg - F.Rabii; H.Ghassemi; S.Vaghefi (Tehran University of Medical Sciences, 1982)
The physiological effects of a diet free of meat and eggs were studied. Fifteen adult lacto-vegetarians were matched with non-vegetarian individuals by age, sex, body weight and height. A two-week dietary record was secured from each individual. The food consumed over a 48-hour period was measured. Venous blood samples were taken from each individual for determination of serum total protein, urea, serum creatinine, hematocrit, hemoglobin and serum cholesterol. In the vegetarians, hemoglobin, hematocrit and serum protein levels were normal; e.g. same as the nonvegetarian controls, but their blood urea level was lower for the same protein intake and their serum cholesterol, was also lower.